PENEGAKAN HUKUM PIDANA BAGI PELAKU PENYEBAR KONTEN PORNOGRAFI DI MEDIA SOSIAL DITINJAU DARI UNDANG-UNDANG INFORMASI DAN TRANSAKSI ELEKTRONIK - Gomgom T.P Siregar; Indra Purnanto S. Sihite (JURNAL RECTUM: Tinjauan Yuridis Penanganan Tindak Pidana, 2021)
The handling of cases of spreading pornographic photos through the social media Facebook is not subject to temporary detention when conducting an investigation because based on the investigator's belief, the perpetrator will not run away, nor will he remove evidence, but what happens is evidence from the perpetrator. Using normative juridical research, which examines the regulations of Law No. 19/2016 on ITE. Criminal law enforcement for perpetrators of spreading pornographic content on social media in terms of the Law on Information and Electronic Transactions Article 45 paragraph 1 of Law No. 19 of 2016 on ITE, the threat of punishment for the perpetrators of dissemination can be sentenced to a maximum imprisonment of 6 years and a maximum fine of Rp. 1,000,000,000 billion.